ASSOCIATIONS OF PIT-1 GENE POLYMORPHISM WITH MILK YIELD AND COMPOSITION TRAITS IN BROWN SWISS CATTLE - İ. Aytekin; S. Boztepe (Journal of Animal and Plant Sciences, 2013)
The present study investigated the genetic variability of Pit-1 polymorphisms (HinfI_451 bp) in a total of 301 Brown Swiss cattle, and also evaluated the possible association between the Pit-1 genotypes and dairy traits such as 305 days milk yield (MY305), test day milk yield (TDMY), fat (%), protein (%), lactose (%), density (kg/m3), solids-non-fat (%), total solids (%), freezing point (oC), and also pH and conductivity (uS/cm) of milk. Allele frequencies were found as A: 0.374 and B: 0.626 in HinfI (451 bp) polymorphism in Pit–1 gene. No significant difference was detected between the observed and the expected genotype frequencies via Hardy-Weingberg equilibrium (P>0.05). The effect of Pit-1 polymorphisms (HinfI_451 bp) was not observed on milk yield and composition in Brown Swiss populations (P>0.05). The results demostrated that the Pit-1 polymorphisms (HinfI_451 bp) could not be exploited as a candidate gene for selection of dairy traits in Brown Swiss cattle.
Keywords: Brown Swiss; Pit-1 (HinfI) polymorphism; RFLP; Milk yield and components